Virtual Platforms and its Use to Teach and Learn English Online - Basantes-Arias, Elsa Amalia; Barros-Leyva, Marienny; Caiza-Mora, Carolina Aracelly; Cuero-González, Olayis Verónica (Dominio de las Ciencias, 2022)
The main aim of this study was to determine the benefits in the application of virtual platforms for English language teaching-learning. The methodology used was quali-quantitative, supported by exploratory, descriptive, explanatory, historical and analytical methods. The main results showed that virtual platforms were undoubtedly a fundamental tool in teaching a second language, due to the resources they possess for communicative interaction between teachers and students. The main focus was to promote a teaching and learning environment that helps the development of talent, creativity and intelligence, according to the individual differences and educational needs of each student and that achieves meaningful learning in order to use the English language efficiently to promote a fluent communication.